Assessing the readiness of health facilities for diabetes and cardiovascular services in Bangladesh: A Cross-sectional survey - Biswas, Tuhin; Haider, M Moinuddin; Gupta, Rajat Das; Uddin, Jasim (BMJ Open, 2022)
This article was published in the BMC Nephrology [© Author(s) (or their employer(s)) 2018. Re-use permitted under CC BY-NC. No commercial re-use. See rights and permissions. Published by BMJ.] and the definite version is available at: 10.1136/bmjopen-2018-022817 The Journal's website is at: https://bmjopen.bmj.com/content/8/10/e022817